LMFP composite positive electrode material and preparation method thereof
By using composite carbon sources (sucrose, polyvinyl alcohol and polystyrene microspheres), the problem of difficulty in obtaining a uniform porous structure in the prior art is solved, and LMFP composite positive electrode materials with high energy density, good rate performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202411574027.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing LiFexMn1-xPO4 (LMFP) electrode material preparation methods are difficult to obtain a uniformly distributed porous agglomeration structure, which limits the formation of three-dimensional interconnected conductive networks, resulting in low electron and ion conduction efficiency, low volume energy density, and poor specific capacity and rate performance.
The LMFP composite positive electrode material is prepared by a composite carbon source. The composite carbon source includes sucrose, polyvinyl alcohol and polystyrene microspheres. Through ball mill mixing and heat treatment, an LMFP composite positive electrode material with suitable carbon content, uniform particle size distribution, porosity and good electrochemical properties are formed.
The high energy density, low electrochemical polarization, good rate performance and good cycle stability of the LMFP composite cathode material are achieved, with high reversible capacity at 0.1C and 5C, and a high capacity retention rate after 200 cycles at 0.5C.
Smart Images

Figure CN119528111A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a LMFP composite positive electrode material and a preparation method thereof. Background Art
[0002] With the rapid depletion of fossil fuels and the increasing environmental pollution, society has an urgent need to develop sustainable energy storage and conversion technologies. Lithium-ion batteries (LI Bs) have gradually become the leader in power solutions for portable electronic devices in the past few decades due to their excellent energy density, long cycle life and small environmental impact. They have received widespread attention and application due to their stable structure, good cycle performance, environmental friendliness and high safety.
[0003] However, its low energy density, insufficient battery life, and slow charging speed limit its large-scale application in the transportation field. 4 In comparison, lithium manganese phosphate (LiMnPO 4 ) due to its higher operating voltage and similar theoretical capacitance, it is theoretically more efficient than LiFePO 4 21% higher energy density, considered to be a potential replacement for LiFePO 4 Commercialization of next generation cathode materials.
[0004] With LiFePO 4 Similarly, lithium manganese phosphate has a stable phosphate oxygen bond and olivine structure, so it releases almost no oxygen during high-temperature charging and discharging, and has high safety performance. x Mn 1-x PO 4 (LMFP) is considered to be a promising alternative to conventional LiFePO 4 This is because LMFP has a high operating voltage (4.1V vs. Li + / L i) and similar theoretical capacity (170 mAh g -1 ), and is higher than LiFePO 4 It has a higher energy density, thus providing a better battery life. At the same time, since LMFP does not contain harmful heavy metal elements such as nickel and cobalt, it reduces the negative impact on the environment.
[0005] Ideal LiFe x Mn 1-x PO 4Electrode materials should have a porous agglomerated structure at the micrometer scale, which is conducive to the manufacture of electrodes and the improvement of volume energy density. However, due to the differences in carbon sources and preparation step parameters, the existing preparation methods have low crystallinity and often make it difficult to obtain a uniformly distributed porous agglomerated structure, which limits the formation of a three-dimensional interconnected conductive network, resulting in low electronic and ion conduction efficiency, low volume energy density of composite materials, and poor specific capacity and rate performance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a LMFP composite positive electrode material and a preparation method thereof.
[0007] The technical solution of the present invention to solve the above technical problems is as follows:
[0008] The invention provides a method for preparing a LMFP composite positive electrode material, which is characterized in that a composite carbon source is used to prepare the LMFP composite positive electrode material, wherein the composite carbon source comprises sucrose, polyvinyl alcohol and polystyrene microspheres.
[0009] Based on the above technical solution, the present invention can also be improved as follows.
[0010] Furthermore, the LMFP composite positive electrode material is LiMn 1-x Fe x PO 4 / C, the value of x is 0.2~0.5.
[0011] Further, the following steps are included:
[0012] S1. Weigh a manganese source, an iron source, and a phosphate salt according to a certain ratio, mix them with sucrose and polystyrene microspheres by ball milling, and add a polyvinyl alcohol solution and anhydrous ethanol to obtain a precursor slurry;
[0013] S2, centrifuging the precursor slurry to obtain a solid mixture;
[0014] S3. After drying the solid mixture, calcining, heating and cooling are performed to obtain the LMFP composite positive electrode material.
[0015] Furthermore, the mass ratio of sucrose, polyvinyl alcohol and polystyrene microspheres is 6-10:4-6:4-6.
[0016] Furthermore, the manganese source is manganese oxalate, the iron source is ferrous oxalate, and the phosphate salt is lithium dihydrogen phosphate.
[0017] Furthermore, in the step S1, the manganese source, the iron source, and the phosphate salt are first mixed with sucrose for ball milling, and then the polystyrene microspheres are added for further ball milling, and finally the polyvinyl alcohol solution and anhydrous ethanol are added for further ball milling.
[0018] Furthermore, in step S3, the calcination is carried out in an argon atmosphere, the calcination temperature is 400°C to 440°C, and the calcination time is 4 to 6 hours; the heating temperature is 630°C to 670°C, and the heating time is 6 to 10 hours.
[0019] Furthermore, the preparation method of the polystyrene microspheres comprises the following steps:
[0020] Polyvinyl pyrrolidone and water are mixed to obtain a prepolymer mixture; styrene monomer is added to the prepolymer mixture and heated to obtain an emulsion; an initiator is added to the emulsion to cause a polymerization reaction in the emulsion; after the polymerization reaction is completed, washing, precipitating and drying are performed to obtain the polystyrene microspheres.
[0021] The present invention also provides a LMFP composite positive electrode material, which is prepared by the above method.
[0022] The present invention also provides a lithium battery prepared by using the above-mentioned LMFP composite positive electrode material.
[0023] The beneficial effects of the present invention are:
[0024] (1) The preparation method of the LMFP composite cathode material of the present invention can obtain a LMFP composite cathode material having a suitable carbon content, uniform particle size distribution, porosity and good electrochemical performance by using a composite carbon source (sucrose, PVA and a certain amount of polystyrene microspheres);
[0025] (2) The preparation method of the LMFP composite positive electrode material of the present invention has simple steps, mild conditions, low cost, no need to introduce highly toxic chemicals, and has good environmental protection characteristics;
[0026] (3) The preparation method of the LMFP composite cathode material of the present invention provides a reasonable approach for designing and preparing other olivine-based cathode materials with high energy / power density;
[0027] (4) The LMFP composite cathode material of the present invention has high energy density, small electrochemical polarization, good rate performance and good cycle stability, high reversible capacity at 0.1C and 5C, and high capacity retention rate after 200 cycles at 0.5C rate at room temperature;
[0028] (5) The LMFP composite cathode material of the present invention has an optimized pore structure and a smaller primary particle size, which can effectively shorten the diffusion distance of lithium ions and increase the specific surface area. The uniform carbon coating can improve the electron transport capacity and reduce the electrochemical polarization. The well-crystallized particles and high purity ensure the stability of the structure over a long period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The preparation method of the LMFP composite positive electrode material of the present invention, the porous LiMn 0.8 Fe 0.2 PO 4 / Schematic diagram of the preparation process of C microagglomerates;
[0030] Figure 2 a is the preparation method of the LMFP composite positive electrode material of the present invention. In Example 2, different carbon sources LiMn 0.8 Fe 0.2 PO 4 Raman spectra of / C materials; Figure 2 b is the different carbon sources LiMn in Example 2 0.8 Fe 0.2 PO 4 XRD patterns of / C samples;
[0031] Figure 3 The preparation method of the LMFP composite positive electrode material of the present invention, in Example 3, different carbon sources LiMn 0.8 Fe 0.2 PO 4 / C material SEM analysis diagram, Figure 3 a in the middle is LMFP-82, Figure 3 b in the middle is LMFP-PVA, Figure 3 c in the figure is LMFP-PS, Figure 3 d in the middle is LMFP-PVA-PS;
[0032] Figure 4 The preparation method of the LMFP composite positive electrode material of the present invention, in Example 4, the transmission electron microscope image of LMFP-PVA-PS, Figure 4 The scale bar in a is 100 nm. Figure 4 The scale bar in b is 5 nm;
[0033] Figure 5 The preparation method of the LMFP composite positive electrode material of the present invention, in Example 5, different carbon sources LiMn 0.8 Fe 0.2 PO 4 TG diagram of / C material;
[0034] Figure 6 The XPS analysis chart of Example 6 is the preparation method of the LMFP composite positive electrode material of the present invention. Figure 6 a in the middle is the full spectrum of LMFP-PVA-PS, Figure 6 b is the high-resolution ion XPS spectrum of Mn2p. Figure 6c is the high-resolution ion XPS spectrum of Fe2p. Figure 6 In the figure, d is the high-resolution ion XPS spectrum of C1 s. Figure 6 e in the figure is the high-resolution ion XPS spectrum of O1 s;
[0035] Figure 7 The preparation method of the LMFP composite positive electrode material of the present invention, in Example 7, different carbon sources LiMn 0.8 Fe 0.2 PO 4 Electrochemical performance analysis diagram of / C materials, Figure 7 a in the figure is the cycling performance at different rates from 0.1C to 5C. Figure 7 b is the performance after 200 cycles at 0.5C rate. Figure 7 c is the charge and discharge curve at 0.1C. Figure 7 Figure d is the charge and discharge curves at different rates from 0.1C to 5C;
[0036] Figure 8 a is the preparation method of the LMFP composite positive electrode material of the present invention. In Example 7, different carbon sources LiMn 0.8 Fe 0.2 PO 4 EIS diagram of / C material, Figure 8 b in the figure represents different carbon sources LiMn 0.8 Fe 0.2 PO 4 / C material at 0.1mV·s -1 Cyclic voltammetry curves at scan rate. DETAILED DESCRIPTION
[0037] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0038] The method for preparing the LMFP composite positive electrode material of the invention adopts a composite carbon source to prepare the LMFP composite positive electrode material, and the composite carbon source comprises sucrose, polyvinyl alcohol and polystyrene microspheres.
[0039] The preparation method of the LMFP composite positive electrode material of the present invention can obtain the LMFP composite positive electrode material with suitable carbon content, uniform particle size distribution, porosity and good electrochemical performance. The thermal decomposition characteristics of sucrose and polyvinyl alcohol provide a uniform carbon coating for each primary particle, and the decomposition of polystyrene microspheres provides necessary pores for the particles. These pores are not only conducive to the distribution of electrolytes, but also can shorten the diffusion path of lithium ions, laying a foundation for improving the electrochemical performance of the material.
[0040] Preferably, the LMFP composite cathode material is LiMn 1-x Fe x PO 4 / C, the value of x is 0.2~0.5.
[0041] More preferably, the value of x is 0.2, and the LMFP composite positive electrode material is LiMn 0.8 Fe 0.2 PO 4 / C, the micro-agglomeration preparation process is as follows Figure 1 shown.
[0042] When synthesizing lithium manganese iron phosphate, the manganese-iron ratio, that is, the molar ratio of manganese to iron, has an important influence on the material's structure, crystal morphology, electrochemical activity, etc., which in turn affects the battery performance; when the manganese-iron ratio is 8:2, the structure of the prepared material is the most stable, the particles are in a micro-agglomerated state, and have the best electrochemical performance.
[0043] Preferably, the ratio of the total mass of the composite carbon source to the manganese source, the iron source and the phosphate salt is 0.06-0.13:1.
[0044] The preparation method of the LMFP composite positive electrode material of the present invention specifically comprises the following steps:
[0045] S1. Weigh a manganese source, an iron source, and a phosphate salt according to a certain proportion, mix them with sucrose and polystyrene microspheres by ball milling, and simultaneously add a polyvinyl alcohol solution and anhydrous ethanol to obtain a precursor slurry.
[0046] Preferably, the mass ratio of sucrose, polyvinyl alcohol and polystyrene microspheres is 6-10:4-6:4-6.
[0047] Preferably, the manganese source is manganese oxalate (Mn(CH 3 COO 2 ), the iron source is ferrous oxalate (Fe(CH 3 COO 2 ), the phosphate salt is lithium dihydrogen phosphate (LiH 2 PO 4 ).
[0048] Further preferably, when the LMFP composite positive electrode material is Li Mn 0.8 Fe 0.2 PO 4 / C, Mn:Fe:PO is 0.8:0.2:1, specifically, manganese oxalate (Mn(CH3COO)2) is 0.032 mol, ferrous oxalate (Fe(CH 3 COO 2 ) is 0.008 mol, and lithium dihydrogen phosphate (LiH2PO4) is 0.04 mol.
[0049] Preferably, the manganese source, the iron source and the phosphate salt are first mixed with sucrose for ball milling, and then polystyrene microspheres are added for further ball milling, and finally polyvinyl alcohol solution and anhydrous ethanol are added for further ball milling.
[0050] More preferably, the manganese source, the iron source, and the phosphate salt are first ball-milled with sucrose for 5 hours, polystyrene microspheres are added and ball-milled for 3 hours, and then polyvinyl alcohol is added and ball-milled for 2 hours.
[0051] S2, centrifuging the precursor slurry to obtain a solid mixture;
[0052] S3. After drying the solid mixture, calcining, heating and cooling are performed to obtain a LMFP composite positive electrode material.
[0053] Preferably, the calcination is carried out in an argon atmosphere, the calcination temperature is 400° C. to 440° C., and the calcination time is 4 to 6 hours; the heating temperature is 630° C. to 670° C., and the heating time is 6 to 10 hours.
[0054] In the method of the present invention, the polystyrene microspheres used may be commercially available or prepared.
[0055] The preparation method of polystyrene microspheres comprises the following steps:
[0056] The polyvinyl pyrrolidone and water are mixed to obtain a prepolymer mixture; styrene monomer is added to the prepolymer mixture and heated to obtain an emulsion; an initiator is added to the emulsion to cause a polymerization reaction of the emulsion; after the polymerization reaction is completed, washing, precipitating and drying are performed to obtain polystyrene microspheres.
[0057] Preferably, the initiator is V-50, the heating temperature is 70° C., and the heating method is an oil bath. At the same time, the polymerization reaction is also carried out in a 70° C. oil bath in a nitrogen atmosphere, and it is necessary to ensure that the reaction environment is stable and oxygen is not involved.
[0058] The specific processing steps after the completion of the polymerization reaction are to wash the precipitate with a large amount of water to remove the unreacted monomers and initiators in the reaction system, and continue to wash until the solution is neutral to ensure the purity of the nanospheres. Finally, the collected polystyrene nanospheres are washed with ethanol and then dried overnight in a vacuum environment at 60°C to obtain dry nanosphere products.
[0059] The LMFP composite positive electrode material of the present invention is prepared by the method as described above.
[0060] The LMFP composite positive electrode material has high energy density, small electrochemical polarization, good rate performance and good cycle stability. 0.8 Fe 0.2 PO4 The reversible capacities of the samples at 0.1C and 5C are 151.3 mAh·g -1 and 106.2mAh·g -1 The capacity retention rate after 200 cycles at 0.5C rate at room temperature is 96.6%.
[0061] The composite material prepared by the method of the present invention has an optimized pore structure and a smaller primary particle size, which can effectively shorten the diffusion distance of lithium ions and increase the specific surface area. The uniform carbon coating can improve the electron transmission capacity and reduce the electrochemical polarization. The well-crystallized particles and high purity ensure the stability of the structure over a long period. This provides a reasonable way to design and prepare other olivine-based positive electrode materials with high energy / power density.
[0062] The lithium battery of the present invention is prepared by using the above-mentioned LMFP composite positive electrode material.
[0063] The present invention is illustrated below by means of specific examples.
[0064] Example 1 Preparation of LMFP composite material
[0065] This embodiment adopts the method of the present invention to prepare the LMFP composite material, and the specific process is as follows:
[0066] (1) Preparation of polystyrene microspheres.
[0067] 0.16 g of polyvinyl pyrrolidone (PVP) was dissolved in 100 ml of deionized water and stirred vigorously to ensure uniform dispersion. The solution was stirred for 30 minutes under a nitrogen atmosphere to form a prepolymer mixture.
[0068] 10 ml of styrene monomer was added to the above mixture, and it was placed in an oil bath at 70 ° C for further heating for 30 minutes, during which the mixture turned into a white emulsion. This process is the preliminary stage of emulsion polymerization and is ready for the polymerization reaction. Subsequently, a 1.3 mol aqueous solution containing 0.2 g of V-50 initiator was slowly added to the emulsion. The entire polymerization reaction was carried out at 70 ° C in a nitrogen atmosphere to ensure that the reaction environment was stable and there was no oxygen involved, and it lasted for 24 hours. After the polymerization was completed, the precipitate was rinsed with a large amount of water to remove the unreacted monomers and initiators in the reaction system, and the solution was continuously rinsed until it was neutral to ensure the purity of the nanospheres. Finally, the collected polystyrene nanospheres were washed with ethanol and then dried overnight in a vacuum environment at 60 ° C to obtain a dry nanosphere product.
[0069] (2) LiMn 0.8 Fe 0.2 PO 4Preparation of C / C composite cathode materials
[0070] First, 0.3 g of polyvinyl alcohol was dissolved in 5 ml of deionized water and set aside according to the stoichiometric ratio of manganese source: iron source: phosphate (Mn:Fe:PO 4 )=0.8:0.2:1 Weigh 0.032mol manganese oxalate (Mn(CH 3 COO 2 ), 0.008 mol of ferrous oxalate (Fe(CH 3 COO 2 ) and 0.04 mol lithium dihydrogen phosphate (LiH 2 PO 4 ).
[0071] The above substances and sucrose were added to a zirconia ball mill for ball milling and mixing. After 5 hours of ball milling, polystyrene microspheres were added to the ball mill for continuous ball milling for 3 hours, and the prepared polyvinyl alcohol solution and 25 ml of anhydrous ethanol were added, and then ball milling was continued for another 2 hours.
[0072] After the precursor slurry was centrifuged, the solid mixture was dried in a vacuum at 80°C for 1 hour. After the precursor was completely ground, it was calcined at 420°C for 5 hours in a tube furnace in an argon atmosphere, then heated to 650°C for 8 hours, and then naturally cooled to room temperature to obtain a lithium iron manganese phosphate sample, which was recorded as LMFP-PVA-PS.
[0073] In this embodiment, the amount of sucrose is 0.16 g, the amount of polyvinyl alcohol is 0.1 g, and the amount of polystyrene microspheres is 0.1 g.
[0074] In addition, for comparison, LMFP-82, LMFP-PVA, and LMFP-PS were prepared using the same steps and parameters, respectively. LMFP-82 used only sucrose as a carbon source, and the amount of sucrose was 0.36 g. LMFP-PVA used only polyvinyl alcohol as a carbon source, and the amount of polyvinyl alcohol was 0.22 g. LMFP-PS used only polystyrene microspheres as a carbon source, and the amount of polystyrene microspheres was 0.25 g.
[0075] Example 2 XRD and Raman analysis of composite materials
[0076] Figure 2 a is LiMn synthesized from different carbon sources prepared in Example 0.8 Fe 0.2 PO 4 Raman spectrum of the / C sample. Raman spectroscopy analysis reveals that LiMn 0.8 Fe 0.2 PO 4 / C composites at 1330cm-1 and 1590cm -1 The two peaks represent the defect-intensive region of amorphous carbon (D band) and the plane vibration of graphite-like carbon (G band). The intensity ratio of D band to G band (I D / I G ) is used as a quantitative indicator to evaluate the degree of graphitization of carbon materials, among which the lower I D / I G The ratio reflects a relatively higher sp2 hybridized carbon content, which is associated with higher electrical conductivity and degree of graphitization.
[0077] I of LMFP-PVA-PS, LMFP-PVA, LMFP-PS and LMFP-82 D / I G The ratios are 0.89, 0.90, 0.97 and 1.08, respectively, indicating that LMFP-PVA-PS exhibits the highest graphitization level, indicating excellent electrical conductivity. -1 The Raman scattering peak near is weak, which is PO 4 3- The characteristic peaks of anion vibration indicate that the anion is uniformly distributed in the composite material. Considering that the mass fractions of carbon in the four samples are close, the low I D / I G The ratio may also indicate a more uniform carbon distribution.
[0078] Figure 2 Figure b is the X-ray diffraction (XRD) diagram of each sample. It can be seen from the figure that the composite material has a single orthorhombic olivine structure, and the main diffraction peaks are highly consistent with the standard PDF card 74-0375, and no other impurity phases are observed. The sharpness and high intensity of the diffraction peaks characterize the high crystallinity of the sample. The lack of identifiable carbon diffraction peaks indicates that the carbon introduced during the synthesis process exists in a disordered state, which may be obtained during the carbonization process. From the entire XRD spectrum, it can be seen that the added carbon has a significant effect on the LiMn 0.8 Fe 0.2 PO 4 / The lattice structure of C has no effect.
[0079] Example 3 SEM analysis of composite materials
[0080] Figure 3 LiMn synthesized using different carbon sources 0.8 Fe 0.2 PO 4 FESEM images of the / C composites.
[0081] In LMFP-82, the aggregation of inhomogeneous spherical nanoparticles indicates a potential disordered growth mechanism during the synthesis process, which may affect the penetration of electrolytes and the transport pathway of lithium ions.
[0082] In LMFP-PS, the fusion of particles and the emergence of porous structures indicate a more dynamic interaction between carbon source decomposition and solid precursors during the synthesis process.
[0083] In LMFP-PVA, the particles exhibited clearer boundaries, indicating the potential differences in the thermal decomposition and material morphology control of the carbon sources used during the synthesis process.
[0084] The uniform particle size and pore structure displayed by the LMFP-PVA-PS sample are the result of highly ordered crystal growth and precise thermal treatment control, which is conducive to the full penetration of the electrolyte and the rapid diffusion of lithium ions in the electrode material. The differences in these structural features, including particle size, porosity, and continuity of the carbon layer, profoundly affect the electrochemical properties of the material. The thermal decomposition characteristics of sucrose and polyvinyl alcohol provide a uniform carbon coating for each primary particle, while the decomposition of polystyrene microspheres provides the necessary pores for the particles. These pores not only facilitate the distribution of the electrolyte, but also shorten the diffusion path of lithium ions, laying the foundation for improving the electrochemical performance of the material.
[0085] Example 4 TEM analysis of composite materials
[0086] In order to further explore the microstructure of LMFP-PVA-PS nanoparticles, transmission electron microscopy (TEM) was used to carry out detailed microscopic characterization. Figure 4 As shown. It can be seen that the LMFP-PVA-PS particles are evenly distributed with a size of about 100nm and are closely connected by the bridging structure of the conductive carbon layer. This in-situ formed carbon coating is not only connected on the surface, but also penetrates deep into the particles to form a continuous conductive network. The carbon network provides an efficient transmission path for electrons, ensuring immediate contact with the active sites of the battery reaction, effectively reducing the migration distance of lithium ions in the electrode, reducing the electrochemical polarization phenomenon, and increasing the available number of active sites. Detailed observation also shows that the composite material exhibits a smaller particle size and slight agglomeration. The carbon layer on the surface of the particles shows good integrity and continuity, and the layer thickness is uniform, which is consistent with the aforementioned scanning electron microscopy (SEM) analysis.
[0087] Example 5 TG analysis of composite materials
[0088] Thermogravimetric analysis (TGA) was performed on the samples under air atmosphere to determine the carbon content of the materials. Figure 5In the TGA curve shown, the temperature was increased from room temperature to 800°C (heating rate was 10°C / min). The analysis results showed that the carbon contents of LMFP-PVA-PS, LMFP-PVA, LMFP-PS and LMFP-82 samples were 4.77%, 4.53%, 4.86%, and 4.36%, respectively.
[0089] Example 6 XPS analysis of composite materials
[0090] Figure 6 This is the XPS spectrum of the LMFP-PVA-PS sample. By analyzing the peaks in the spectrum, the chemical environment of each element in the sample can be determined. At the reference energy of the C1s peak set to 284.8eV, Li 1s, P2p and O1s appear at 55.5eV, 133.9eV and 531.0eV, respectively. These energy positions correspond to the characteristic energy states of lithium, phosphorus and oxygen in the composite material. In particular, the position of P2p indicates that phosphorus exists in the form of phosphate, which is consistent with the LiFePO 4 The LMFP-PVA-PS sample has Mn2p at 653.6 eV. 1 / 2 The spin-orbit splitting component and the spin-orbit splitting.
[0091] Example 7 Electrochemical Performance Analysis of Composite Materials
[0092] The LMFP / C series materials were systematically electrochemically characterized to explore the effects of different carbon sources on their performance.
[0093] Figure 7 Figure a is a rate performance diagram of synthetic materials with different carbon sources. It can be seen from the figure that the LMFP-PVA-PS material shows excellent performance under high-rate discharge conditions, with less energy attenuation and can quickly recover the initial capacity when the rate decreases. This phenomenon shows that the LMFP-PVA-PS material has excellent electronic conductivity and ionic conductivity. In contrast, LMFP-82 and LFMP-PVA show a sharp drop in capacity when the current density increases, indicating that their performance under high-rate discharge conditions is insufficient.
[0094] Figure 7 Figure b is a cycle stability diagram of synthetic materials with different carbon sources. After 200 charge and discharge cycles at a rate of 0.5C, the capacity retention rate of LMFP-PVA-PS reached 97.6%, which is significantly higher than other materials.
[0095] Figure 7Figure c is the charge-discharge curves of different carbon source synthesized materials at 0.1C rate. All materials showed characteristic redox peaks at 3.6 / 3.5V and 4.1 / 4.0V, corresponding to the electrochemical activity of Mn. LMFP and LMFP-PS showed lower specific capacity and significant potential polarization, indicating the poor conductivity and lithium ion transport ability caused by their single carbon source.
[0096] Figure 7 Figure d shows the charge and discharge curves of LMFP-PVA-PS recorded at different rates. The reversible discharge capacities of LMFP-PVA-PS are 151.3, 134.5, 130.6, 124.7, 115.8, and 105.9 mAh·g, respectively. -1 , 0.1, 0.2, 0.5, 1, 2 and 5C respectively. In the charge-discharge curve at 0.1C rate, the LMFP-PVA-PS sample showed 151.3mAh·g -1 The high discharge capacity and stable performance at different rates. After the charge and discharge cycle at high rate, when the current density drops back to low rate, its specific capacity can be well restored, which proves that the material has excellent structural stability even at high current density. From the perspective of material synthesis, the composite carbon source used in the LMFP-PVA-PS sample is crucial to its microstructure, especially the formation of electron and lithium ion transport pathways. This composite strategy achieves precise microstructural regulation by controlling the decomposition of the carbon source, thereby optimizing the electrochemical performance.
[0097] Figure 8 a is the EIS graph of the composite material. Figure 7 b is the composite material at 0.1mV·s -1 Cyclic voltammetry curves at scan rates. EIS analyzed the impedance characteristics of LMFP-82, LMFP-PS, LFMP-PVA and LMFP-PVA-PS in the frequency domain from 0.01 Hz to 100 kHz. The fitted charge transfer impedance (R CT ) values are 335.4Ω, 347.1Ω, 423.8Ω, and 597.1Ω, corresponding to the above four composite materials, respectively. LFMP-PVA-PS exhibits the best charge transfer performance, indicating lower hindrance in the electrochemical reaction, which is coordinated with its high reversibility and excellent rate response.
[0098] This reduced impedance can be traced back to the micro-agglomerate structure formed under the addition and regulation of organic carbon sources, which provides a more convenient migration channel for lithium ions. This microstructural property is positively correlated with the electrochemical performance advantages of the LFMP-PVA-PS electrode, confirming the importance of microstructural regulation in material design.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a LMFP composite positive electrode material, characterized in that: The LMFP composite positive electrode material is prepared by using a composite carbon source, wherein the composite carbon source comprises sucrose, polyvinyl alcohol and polystyrene microspheres.
2. The method for preparing a LMFP composite positive electrode material according to claim 1, characterized in that: The LMFP composite positive electrode material is LiMn 1-x Fe x PO4 / C, the value of x is 0.2~0.
5.
3. The method for preparing a LMFP composite positive electrode material according to claim 2, characterized in that: The following steps are involved: S1. Weigh a manganese source, an iron source, and a phosphate salt according to a certain ratio, mix them with sucrose and polystyrene microspheres by ball milling, and add a polyvinyl alcohol solution and anhydrous ethanol to obtain a precursor slurry; S2, centrifuging the precursor slurry to obtain a solid mixture; S3. After drying the solid mixture, calcining, heating and cooling are performed to obtain the LMFP composite positive electrode material.
4. The method for preparing a LMFP composite positive electrode material according to claim 3, characterized in that: The mass ratio of sucrose, polyvinyl alcohol and polystyrene microspheres is 6-10:4-6:4-6.
5. The method for preparing a LMFP composite positive electrode material according to claim 3, characterized in that: The manganese source is manganese oxalate, the iron source is ferrous oxalate, and the phosphate salt is lithium dihydrogen phosphate.
6. The method for preparing a LMFP composite positive electrode material according to claim 3, characterized in that: In the step S1, the manganese source, the iron source, and the phosphate salt are first mixed with sucrose for ball milling, and then the polystyrene microspheres are added for further ball milling, and finally the polyvinyl alcohol solution and anhydrous ethanol are added for further ball milling.
7. The method for preparing a LMFP composite positive electrode material according to claim 3, characterized in that: In the step S3, the calcination is carried out in an argon atmosphere, the calcination temperature is 400°C to 440°C, and the calcination time is 4 to 6 hours; the heating temperature is 630°C to 670°C, and the heating time is 6 to 10 hours.
8. The method for preparing a LMFP composite positive electrode material according to any one of claims 1 to 7, characterized in that: The preparation method of the polystyrene microspheres comprises the following steps: Polyvinyl pyrrolidone and water are mixed to obtain a prepolymer mixture; styrene monomer is added to the prepolymer mixture and heated to obtain an emulsion; an initiator is added to the emulsion to cause a polymerization reaction in the emulsion; after the polymerization reaction is completed, washing, precipitating and drying are performed to obtain the polystyrene microspheres.
9. A LMFP composite positive electrode material, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: It is prepared using the LMFP composite positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
Lithium iron phosphate suitable for high multiplying power electrokinetic cell and method for producing the same
CN101162776A
Preparation method and application of spherical lithium ferrite material / carbon cathode material composite
CN104393255A
Method of manufacturing lithium manganese iron phosphate / carbon cathode material, and use of lithium manganese iron phosphate / carbon cathode material
CN104681799A
Manufacturing method and use of spinel-structured lithium-nickel-manganese negative electrode material
CN107316991A
Method for manufacturing lithium iron phosphate / carbon composite cathode material for secondary lithium ion battery
EP3770996A1